Enterocytozoon bieneusi and Encephalitozoon intestinalis (microsporidia) in HIV-positive patients in central Spain. (6th April 2023) - Chozas, Mercedes; Dashti, Alejandro; Prieto-Pérez, Laura; Pérez-Tanoira, Ramón; Cobo, Elena; Bailo, Begoña; del Palacio, Marta; Hernández-Castro, Carolina; González-Barrio, David; Carmena, David; Köster, Pamela C
Abstract: Microsporidia are fungi-related eukaryotic intracellular parasites that opportunistically infect immunocompromised individuals such as those infected by the human immunodeficiency virus (HIV). Among them, Enterocytozoon bieneusi and Encephalitozoon spp. are the most clinically relevant species. We investigated the occurrence and genetic diversity of microsporidial and protist infections in mostly immunocompetent HIV-positive patients in Madrid, Spain. A structured questionnaire was used to retrieve data on factors potentially associated with an increased risk of infection, including sexual attitudes and sex-risk behaviour. Faecal samples ( n = 96) from 81 HIV-positive patients were collected and analysed by molecular (PCR and Sanger sequencing) methods. Two microsporidial pathogens were detected: Ent. bieneusi (2.5%, 95% CI: 0.3–8.6) and Enc.intestinalis (4.9%, 95% CI: 1.4–12.2). The two Ent. bieneusi isolates were identified as zoonotic genotype A. Among protists, Entamoeba dispar was the species most prevalently found (33.3%, 95% CI: 23.2–44.7), followed by Blastocystis spp. (19.8%, 95% CI: 11.7–30.1), Giardia duodenalis (13.6%, 95% CI: 7.0–23.0), and Cryptosporidium spp. and Entamoeba histolytica (2.5%, 95% CI: 0.3–8.6 each). Cyclospora cayetanensis and Cystoisospora belli were not detected. Subtypes ST1 (70.6%, 12/17) and ST3 (29.4%, 5/17) were identified within Blastocystis sp., sub-assemblages AII and BIII (50%, 1/2 each) within G. duodenalis, and Cry. parvum and canine-adapted Cry. canis (50%, 1/2 each) within Cryptosporidium spp. Microsporidial and protist parasites were frequent in well-controlled, mostly immunocompetent HIV-positive patients and should be included in diagnostic algorithms when diarrhoea is present. Lay Summary: Opportunistic microsporidial and protist intestinal infections were relatively common in well-controlled HIV-positive patients in Madrid, Spain. These agents should be suspected and appropriately diagnosed in HIV-positive patients presenting with diarrhoea regardless of their immunological status.